The unready queen - Ritter, William, 1984- (Ritter, William, 1984- Oddmire, 2020)
Fable, the half-human daughter of the Queen of the Deep Dark, and her friends, the human and goblin brothers Cole and Tinn, discover that humans are destroying the Wild Wood, breaking the unspoken truce between the people of Endsborough and the inhabitants of the Wild Wood and leading them to war.